Self-sustained all-electric wave energy converter system. Issue 5 (19th August 2014) - Sjolte, Jonas; Tjensvoll, Gaute; Molinas, Marta; Sykulski, Jan; Masmoudi, Ahmed
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose This paper describes the design and function of Fred. Olsens Wave Energy Converter system Lifesaver with special focus on the stand-alone electrical system that is implemented for operation without grid-connection. Design/methodology/approach The paper focus on the detailed design of the DC-Link system that drives the industrial 400 VAC inverters and generators for the production system. The DC-Link is stabilized by an ultracapacitor bank and has no external source or grid-connection. Findings The system has been tested through extensive sea trials since April 2012 and has proved its function. Some results from real sea testing are presented. Practical implications This paper proves the viability of the specied design and may serve as a basis for the design if similar systems in the future. Originality/value This paper presents a Wave Energy Converter system that has proven successful operation through practical tests, and is therefore regarded as a high value paper as there is limited experience on this subject.